2_Probability and Statistics

# 9112012 p kolm 34 an example estimating the population

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: la to calculate q from sample data is called an estimator VER. 9/11/2012. © P. KOLM 34 An Example Estimating the population mean by the sample average n Let us start with the formula for E (X ) = å x i f (x i ) i =1 Since each point has an equal chance of being included in the sample, we 1 for f (x i ) (the probability weight). Then, the sample average for n our sample takes the form substitute 1n ˆ mX º X º å Xi n i =1 We will see many more examples throughout the lecture sequence VER. 9/11/2012. © P. KOLM 35 What Makes a Good Estimator? Some estimators are better than others. The search for good estimators is a big part of econometrics Estimators are compared based on a number of attributes: Unbiasedness Efficiency Mean Square Error (MSE) Asymptotic properties (for large samples) Consistency We discuss each one of these attributes next VER. 9/11/2012. © P. KOLM 36 Unbiasedness Intuition: We want our estimator “to be right on average” ˆ Formally, we say that an estimator, q = h(Y ) , of the parameter q is unbiased if the mean of its sampling distribution is q . Mathematically, this means that ˆ E (q) = q VER. 9/11/2012. © P. KOLM 37 Example: The Sample Mean and Variance Let Y = (Y1,Y2,...,Yn ) be a random sample from a population with mean mY and 2 variance sY 1n The sample mean Y = åYi is unbiased: n i =1 We take the expectation of the sample mean æ1 n ö 1 n 11 ÷= ç E (Y ) = E ç åYi ÷ E (Yi ) = å n mY =mY ÷ ÷ ç n i =1 ø n å n i =1 è i =1 Note: The variance of Y (the sample variance) is given by 2 n æ1 n ö sY 2 ÷= 1 ç ÷ Var (Y ) = Var ç åYi ÷ s= ç n i =1 ÷ n 2 å Y n è ø i =1 Therefore, as n increases Y gets more precise VER. 9/11/2012. © P. KOLM 38 1n The estimator for the variance s = å (Yi -Y )2 is unbiased: n - 1 i =1 First, observe that 2 Y n n å (Yi -Y ) = å ((Yi - mY ) - (Y - mY )) 2 i =1 2 i =1 n n = å (Yi - mY ) - 2(Y - mY )å (Yi - mY ) + n(Y - mY )2 2 i =1 n i =1 = å (Yi - mY )2 - 2n(Y - mY )2 + n(Y - mY )2 i =1 n = å (Yi - mY )2 - n(Y - mY )2 i =1 Therefore, æ1 n ö 2÷ ç E (s ) = E ç (Y -Y ) ÷ ÷ ÷ çn - 1 å i è ø i =1 æ1 n ö n 2÷ ç ÷ E (Y - mY )2 =Eç (Yi - mY ) ÷ å ÷ n -1 ç n - 1 i =1 è ø 2 Y ( ) n n E (Yi - mY )2 E (Y - mY )2 n -1 n -1 2 ææ n öö çç 1 n n ÷÷ çç ÷÷ ÷ = Var (Yi ) E ç å (Yi - mY )÷ ÷ çç ÷÷ ÷ n -1 n - 1 çè n i =1 øø è = VER. 9/11/2012. © P. KOLM ( ) ( ) 39 Since Y = (Y1,Y2,...,Yn ) are iid, we obtain 2 ææ n öö çç 1 n n 2 ÷÷ çç ÷÷ E (sY ) = Var (Yi ) E ç å (Yi - mY )÷ ÷ çç n i =1 ÷÷ n -1 n - 1 çè ø÷ ÷ è ø æ1 n ö n n 2÷ ç = Var (Yi ) E ç 2 å (Yi - mY ) ÷ ÷ ÷ n -1 n - 1 ç n i =1 è ø n n n Var (Yi ) = ⋅ 2 E (Yi - mY )2 n -1 n -1 n n n n Var (Yi ) = ⋅ 2 E (Yi - mY )2 n -1 n -1 n = Var (Yi ) ( ) ( ) which shows the unbiasedness of the estimator. 1n ˆ Note: The estimator s = å (Yi -Y )2 is biased downward. In particular, n i =1 n -1 2 n -1 1 2 ˆ2 ˆ2 s . However, Var (sY ) = 2 2 s 4 < Var (sY ) = 2 E (sY ) = s 4 (For you: n n -1 n Show this.) This means that the biased estimator has a smaller variance. The 2 Y difference is negligible in large samples, but, for example is about 10% in a sample of 16. VER. 9/11/2012...
View Full Document

## This document was uploaded on 02/17/2014 for the course COURANT G63.2751.0 at NYU.

Ask a homework question - tutors are online